Histologic and histomorphometric alterations in the cranial and caudal vaginal mucous membrane of HF cow during follicular and luteal phases of estrus cycle - HASANZADEH, S; AYEN, E; KHALILZADEH, O (The Indian Journal of Animal Sciences, 2014)
Histologic observation revealed that in the cranial region of the vaginal epithelium a surface layer of coiumhar cells are present at both the follicular and luteal phases. These cells were PAS reactive. The mast cells were distributed in all the layers of vagina, but their population were higher in luteal than the follicular phase. There were significant difference (P<0.05) in mean thicknesses of epithelium of cranial vegina at follicular (149.10±3.57um) and luteal (137.64±3.59 um) phases. Also there were significant differences (P<0.05) in mean thicknesses (P<0.05) difference in mean thickness of PAS reactive regions of epithelium between follicular and luteal phases at both the cranial and caudal regions. There were significant differences (P<0.05) in mean epithelial cell lavers of cranial vagina at follicular (5.19±0.39) and luteal (3.92±0.25) phases, and also in caudal vagina at follicular (6.4±0.27) and luteal (4.28±0.35) phases. In conclusion there are significant histologic and histomorphometric alterations in cranial and caudal vaginal mucosa of the cow during follicular and luteal phases of estrus cycle, and this could have applicative value in diagnosing phases of estrus cycle.